Classification of soft-tissue injuries in open femur fractures: Relevant for systemic complications?. Issue 5 (November 2016) - Weber, Christian David; Lefering, Rolf; Dienstknecht, Thomas; Kobbe, Philipp; Sellei, Richard Martin; Hildebrand, Frank; Pape, Hans-Christoph
Abstract : BACKGROUND: A broad range of systemic complications has been described to occur in patients with open major fractures. Various causes have been claimed to play a role. We therefore surveyed a nationwide trauma registry to assess risk factors associated with closed and various types of open femur fractures. METHODS: This was a cohort study in a nationwide population-based prospective database. Inclusion criteria for selection from database are as follows: individuals with femur fracture, age 16 years or older, and survival until primary admission. Main groups included closed and open femur fracture. Patient demographics, injury severity (New Injury Severity Score), surgical fracture management, length of stay, and systemic complications (e.g., multiple organ failure [MOF], sepsis, mortality) were collected and statistically analyzed using SPSS statistics. Multivariate regression analysis was performed to stratify subgroups for the degree of open soft-tissue injury according to Gustilo and Anderson. RESULTS: Among 32, 582 documented trauma victims (January 1, 2002, to December 31, 2010), a total of 5, 761 met the inclusion criteria. Main groups: 4, 423 closed (76.8%) and 1, 338 open femur fractures (23.2%). Open fractures subgroups were divided into I° (334, 28.1%), II° (526, 44.3%), and III° (328, 27.6%). Open fractures were associated with an increased risk of prehospital hemorrhagic shock ( p = 0.01), higher resuscitation requirements ( p < 0.001), MOF ( p = 0.001), and longer in-hospital ( p < 0.001) and intensive care stay ( p = 0.001). While New Injury Severity Score values showed a minor increase per subgroup, the prevalence of MOF, sepsis, and mortality multiplied with the degree of open soft-tissue injury. Especially patients with Type III open femur fractures received mass transfusions (28.2%, p < 0.001), and mass transfusions were identified as independent predictor for sepsis (odds ratio [OR], 2.393; 95% confidence interval [CI], 1.821–3.143; p < 0.001) and MOF (OR, 2.966; 95% CI, 2.409–3.651; p < 0.001). Our data also indicate an increased mortality in patients with open femur managed outside Level I trauma centers (OR, 1.358; 95% CI, 1.018–1.812; p = 0.037). CONCLUSION: Open femur fractures are associated with higher in-hospital complications related to incidence of MOF, associated intensive care unit stay, and hospital days when compared with closed femur fractures. For prevention of in-hospital complications, prompt hemorrhage control, surgical fracture fixation, cautious blood management, and triage to a Level I trauma center must be considered. LEVEL OF EVIDENCE: Epidemiologic/prognostic study, level II.